INFORMASI DATA REKAM MEDIS PASIEN DI RS BEDAH MITRA KABUPATEN LAMONGAN DENGAN METODE NAIVE BAYES DAN CLUSTERING DALAM PENENTUAN PENYAKIT HYPERTENSI - Kemal Farouq Mauladi (Universitas Islam Lamongan, 2017)
Medical records have a very broad sense, not only as a recording activity, but has a notion as a system of medical record recordings that start recording during the patient get medical service, followed by handling medical records file that includes the storage and the release of files from the storage for Serve requests or loans if from patients or for other purposes. Documents of patient medical record data from patient card data, especially patients with hypertension who at the time of control to the partner surgery hospital will from the medical record card document will be scanned or scanned into computer data base as data base storage efficiently and regularly , To then be tested with data mining by using clustering and naive baiyes to determine the number of patients based on the place or area of patients who are frequently treated at the partner surgical hospital.